Calidad en el servicio al cliente de la Compañía INTRA - cantonal Isla de Bejucal S.A. - Bustamante Zurita, Thalia Maribel (2021)
This case study analyzes the quality of the service offered by the Compañía Intracantonal Isla de Bejucal SA in its service to the users of the Isla de Bejucal Parish and its surroundings. Its objective is to structure a case study that allows investigating those factors that affect the satisfaction perceived by customers through the transport service offered by employees, considering the behavior they have towards the customer, the efficiency at the time of providing the service and evaluating those measures taken by the company to achieve comfort and safety of your customers. For the purpose of the methodology, technical-scientific tools were used, such as a survey and interview from which relevant data were obtained to complement the documented information, an interview applied to the manager of the company and the survey developed to a sample of 30 users who acquire with regular transportation service. The results make it possible to identify the weaknesses or deficiencies in the quality of the service that are present in the company.